MODEL PENDIDIKAN KARAKTER RELIGIUS BERBASIS PADA PENGETAHUAN MATEMATIKA SEKOLAH - Kusno Kusno; Joko Purwanto; Makhful Makhful (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
Moral crisis that hit the Indonesian nation in recent years, not only experienced by the non-educated, even now many intellectuals struck. One reason is the education process has not integrate the knowledge and values. So far, the role of knowledge including mathematics no more left brain only serve that only requires logical thinking skills that equip students only smart but do not equip students are smart. This is because mathematics is the cornerstone of scientific thinking which is separated from the value, but it affects the attitudes and behavior of people in decisions and actions. If early planting religiosity values elaborated with knowledge of Mathematics, it will give birth to light pious people who can bring change to glory. The purpose of this study was decrypt the prototype model of a religious character education based on knowledge of school mathematics. This study uses a model of the 4D development Thiagarajan consisting of Define, Design, Develop and Desseminate. The subject of the study was mathematics schools and Instructional Materials Development (PBA), which developed into a religious character-based educational materials school math knowledge. While the test subjects are mathematics education students who have taken the PBA in the year 2013/2014. Expected results of research are educational teaching materials produced prototypes built religious character of the school of mathematical knowledge. Keywords: moral crisis, secularism, Mathematics, Islamic, Muslim intellectuals